2009
DOI: 10.1002/chem.200802456
|View full text |Cite
|
Sign up to set email alerts
|

A New Quantum Chemical Approach to the Magnetic Properties of Oligonuclear Transition‐Metal Complexes: Application to a Model for the Tetranuclear Manganese Cluster of Photosystem II

Abstract: The reliable correlation of structural features and magnetic or spectroscopic properties of oligonuclear transition-metal complexes is a critical requirement both for research into innovative magnetic materials and for elucidating the structure and function of many metalloenzymes. We have developed a novel method that for the first time enables the extraction of hyperfine coupling constants (HFCs) from broken-symmetry density functional theory (BS-DFT) calculations on clusters. Using the geometry-optimized tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
255
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 129 publications
(266 citation statements)
references
References 101 publications
11
255
0
Order By: Relevance
“…[24] It was shown that the BS approach reproduces the electron density of the system of coupled spins correctly, while the obtained spin densities and thus the EPR parameters could be incorrect. The fact that Fe 6 S 6 models result in almost the same hyperfine coupling constants as Fe 2 S 2 models shows that BS DFT predicts "intrinsic" hyperfine coupling constants rather than the "effective" ones.…”
Section: Corrections To the Bs Solutionsmentioning
confidence: 98%
“…[24] It was shown that the BS approach reproduces the electron density of the system of coupled spins correctly, while the obtained spin densities and thus the EPR parameters could be incorrect. The fact that Fe 6 S 6 models result in almost the same hyperfine coupling constants as Fe 2 S 2 models shows that BS DFT predicts "intrinsic" hyperfine coupling constants rather than the "effective" ones.…”
Section: Corrections To the Bs Solutionsmentioning
confidence: 98%
“…The double-hybrid B2PLYP functional also affords accurate predictions, particularly for HFCs of metal nuclei, but the existence of outliers suggests that this method may lack stability. The reliable performance of the TPSSh functional has since received additional confirmation in our recent study (Pantazis et al 2009) aimed at the analysis of hyperfine coupling parameters in tetramanganese models of the OEC. A topical application of DFT for the determination of EPR parameters, highlighting the capabilities of the broken-symmetry approach, was the study of the trapped-…”
Section: Epr Spectroscopymentioning
confidence: 89%
“…In a recent contribution (Pantazis et al 2009), we investigate the magnetic properties of a tetramanganese complex bearing resemblance to the OEC of PSII (Fig. 3).…”
Section: Exchange Couplingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This spin scheme was considered in this work once HS OEC structures are well described in literature as the main spin scheme found in natural OEC. 5,6,26 We considered initially S0 with zero charge and the following states given in Table 1, according to Kok Cycle scheme, where we can check the different spin/charge arrangements considered in our calculations. For these structures all calculations were performed using the software package Gaussian 09.…”
Section: Methodsmentioning
confidence: 99%